Varietal Screening of Okra (Abelmoschus esculentusl. Moench ) Against Okra Yellow Vein Mosaic Virus Under Different Management Practices at Paklihawa, Rupandehi, Nepal - Poudel, R.; Pandey, A.; Poudel, K.; Chaudhary, A.; Ghimire, N.; Ghimire, S. (Journal of the Institute of Agriculture and Animal Science, 2018)
The experiment was conducted in the Horticulture farm of Institute of Agriculture and Animal Science, Paklihawa, Rupandehi, Nepal from March, 2017 to June, 2017 to screen the varieties of okra against Okra yellow vein mosaic virus under different management practices. The experiment was laid out in two factorial Split plot design and replicated three times. Five varieties of okra viz. Parvati, Arka Anamika, NOH-15, Super Green and Julie were used and five treatments viz. Jholmol (1:5), Azadiracthin (5ml/L), Imidacloprid (2ml/L), cow milk (100ml/L) and control (distilled water) were used as foliar spray on plants. The chlorophyll content of the leaves was higher in Julie followed by Arka Anamika. The white fly count was found to be reduced after the application of treatments in the succeeding date in almost all varieties. The efficiency of the management practices was found to be significant with Super Green and Julie varieties with least Percent Disease Incidence(PDI) value and in par with each other. Imidacloprid and Azadiractin had the leastPDI value and the combination of Super Green variety with Imidacloprid, Super Green with Jholmol, Super Green with cow milk, Julie with Imidacloprid, NOH-15 with Imidacloprid were found resistant. Similarly, the highest yield was obtained in Julie with Imidaclropid combination. However, due to the maximum waiting period of this chemical as well as its negative impact on human and plant health, Julie with Azadirachtin combination can be suggested to farmers to have eco-friendly management of Okra yellow vein mosaic virus.